Modified zero inflated poisson regression analysis and its application to public health data - Wan Ahmad, Wan Muhamad Amir; Zafakali, Nur Syabiha; Aleng, Nor Azlida; Mohd Ibrahim, Mohamad Shafiq; Hasan, Ruhaya; Mokhtar, Kasypi (Pushpa Publishing House, 2019)
This paper focuses on the programming of zero inflated Poisson regression (ZIPR) with combination of fuzzy regression method through SAS algorithm. This alternative method can be used as a tool of data analysis in various branches of science that include biostatistics, biometry. The method comprises of bootstrapping and nonlinear minimization programming through fuzzy linear regression modeling based on the dependent outcome of zero-inflated Poisson regression with several independent variables.